Pretreatment for the recovery of spent lithium ion batteries: theoretical and practical aspects. (1st August 2020) - Zhong, Xuehu; Liu, Wei; Han, Junwei; Jiao, Fen; Qin, Wenqing; Liu, Tong
Abstract: The mechanism and application of a safe and clean process of pretreatment for the disposal of spent lithium ion batteries (LIBs) were investigated in this study. Crushing experiments indicate that spent LIBs can be crushed without discharging using a refitted shear crusher. To remove and recycle the electrolytes, the crushed LIBs were subjected to low-temperature volatilization at 120 °C for 150 min. The results of gas chromatography-mass spectrometry analysis indicated that 99.32% of organic electrolytes and 99.93% of LiPF6 were recycled from the LIBs via volatilization. X-ray diffraction and X-ray photoelectron spectroscopy analyses indicated that a little quantity of organic electrolytes was retained in the solid products after volatilization. Meanwhile, LiNi0.5 Mn0.3 Co0.2 O2 and C were not destroyed, and the F elements contained in the solid products mainly existed in the form of harmless LiF and polyvinylidene difluoride. Finally, industrial-scale experiments shown that the pretreatment is a promising technology for recycling of spent LIBs. Graphical abstract: Image 1 Highlights: Clean crushing and low-temperature volatilization were used to deal with spent LIBs. The crushing of spent LIBs can be achieved by a refitted shear crusher. Hazardous materials can be treated by low-temperature volatilization process. The pretreatment processes can be used in industrial production.